Nursing in nutritional support in cancerpatients – case study - Kristová, Jarmila; Miklovičová, Emília; Bachratá, Zuzana; Solárová, Martina (Nursing in the 21st Century, 2025)
Aim. Malnutrition is a serious problem for cancer patients. Material and methods. We chose a qualitative research method called case study. A semi-structured interview was conducted with the patients, focusing on changes in the satisfaction of nutritional needs arising from the impact of the disease. The interview was complemented by patient observation and his physical screening examination. We also used standardised measurement tools. Results. In terms of nutritional status, a nursing diagnosis of Nutritional Imbalance: a deficiency of nutrients with respect to the body’s requirements was identified in all three cases. As for the fluid intake, the Risk for deficient fluid intake was determined in all cases. Based on the nursing diagnoses, we planned nursing interventions aimed at eliminating the patients’ problems. Prior to discharge to home care, patients were educated by the nurse on nutritional interventions and fluid intake. Comparison of outcomes on admission and after 11 weeks demonstrated improvement in nutritional status and fluid balance in all 3 cases. Conclusions. For effective systematisation of nutritional support in cancer patients, we recommend nurses to use the nursing intervention algorithm. The implementation of the nursing intervention algorithm into practice, confirmed its impact on the elimination of the development of malnutrition in cancer patients.